2018
DOI: 10.1038/s41431-018-0111-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between cancer family history and ovarian cancer risk in BRCA1/2 mutation carriers: can it be explained by the mutation position?

Abstract: This observational study aimed to investigate whether the reported association between family history (FH) of breast cancer (BC) or ovarian cancer (OC) and OC risks in BRCA1/2 mutation carriers can be explained by mutation position on the gene. In total, 3310 female BRCA1/2 mutation carriers participating in a nationwide prospective cohort (Hereditary Breast and Ovarian Cancer in the Netherlands) were included. FH was classified according to cancer occurrence in first-degree relatives (BC only, OC only, both, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Several studies showed a strong correlation between specific BRCA1/2 variants and changes in BC/OC relative risk, by identifying specific putative Breast Cancer Cluster Regions (BCCRs) and Ovarian Cancer Cluster Regions (OCCRs) located on the coding DNA sequences of BRCA1/2 genes (30)(31)(32)(33)(34). As regards the gene location of BRCA1 variants detected in our study cohort, most of them (14/21) were mainly located within the hypothetical cluster region present in the BRCA1 protein structure which includes the exon 11 (nucleotides: 861-4,218; codons: 248-1,366), with a greater distribution inside the serine cluster domain (SCD).…”
Section: Detection Of Germline Brca1/2 Vus In Bc or Oc Patientsmentioning
confidence: 99%
“…Several studies showed a strong correlation between specific BRCA1/2 variants and changes in BC/OC relative risk, by identifying specific putative Breast Cancer Cluster Regions (BCCRs) and Ovarian Cancer Cluster Regions (OCCRs) located on the coding DNA sequences of BRCA1/2 genes (30)(31)(32)(33)(34). As regards the gene location of BRCA1 variants detected in our study cohort, most of them (14/21) were mainly located within the hypothetical cluster region present in the BRCA1 protein structure which includes the exon 11 (nucleotides: 861-4,218; codons: 248-1,366), with a greater distribution inside the serine cluster domain (SCD).…”
Section: Detection Of Germline Brca1/2 Vus In Bc or Oc Patientsmentioning
confidence: 99%
“…The association between an FH of EOC and a personal history of EOC did not reach statistical significance ( p : .076). The role of an FH of EOC as a predictor of EOC risk is already demonstrated, especially among BRCA1 mutation carriers (Texeira et al, 2018 ); this is highly relevant considering that EOC is the third most common gynecologic cancer and has the worst prognosis and the highest mortality rate (Bray et al, 2018 ; Coburn et al, 2017 ; Momenimovahed et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
“…[ 3 , 4 ] Family history is a well-established risk factor for both cancers. [ 5 , 6 ] Compared to the women without a first-degree relative with breast cancer, those with a family history of breast cancer in first-degree relatives had a 2.1 times greater risk of developing breast cancer. [ 7 ] Women with a family history of ovarian cancer in first-degree relatives had a 3.1 times greater risk of developing ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%